2015
DOI: 10.1016/j.jeurceramsoc.2015.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Microcantilever investigation of fracture toughness and subcritical crack growth on the scale of the microstructure in Al 2 O 3

Abstract: Knowledge of the fracture characteristics of individual microstructural features such as grains and grain boundaries is essential for a full understanding of the macroscopic behaviour of ceramics. We have investigated the fracture of single crystal, bicrystal and polycrystalline Al2O3 on the micrometre scale by testing microcantilevers containing notches and artificial flaws introduced at features of interest (e.g. grain boundaries) using focused ion beams (FIB). The specimens were loaded to fracture using a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 33 publications
3
27
0
Order By: Relevance
“…18) This equation is valid when x  b. For the MCL A7, P and x are found to be 750 μN and 0.83 μm, respectively, from the load-displacement relation in Fig.…”
Section: Fracture Toughnessmentioning
confidence: 91%
See 1 more Smart Citation
“…18) This equation is valid when x  b. For the MCL A7, P and x are found to be 750 μN and 0.83 μm, respectively, from the load-displacement relation in Fig.…”
Section: Fracture Toughnessmentioning
confidence: 91%
“…12,18,19) The load reduction rate with respect to the displacement is regarded as a crack propagation rate with respect to given strain. It turns out from the present microbending test results that the HE crack propagates more easily in the direction parallel to the α-θ interface than normal to the α-θ interface.…”
Section: Microbending Testmentioning
confidence: 99%
“…The depth of penetration of Ga ions varies with the FIB voltage and has not been measured in glass to the knowledge of the present authors, but has been shown to be about 20 nm for Al 2 O 3 . 27 The presence of Ga may impact the thermodynamics and kinetics of the aging process. Second, the residual stresses produced during the FIB process 38 may be different in magnitude and distribution from those in natural flaws which are typically produced by contact events.…”
Section: Resultsmentioning
confidence: 99%
“…24,25 A Griffith flaw is defined as a flaw for which the strength is inversely proportional to the square root of the flaw size. 26 It is reasonable to assume that such a small Griffith crack exists at the base of the FIB notch, 27 even if the notch itself is not a Griffith flaw. The relation between the mirror radius, r, and fracture strength, σ f , is given by…”
Section: Mechanical Testingmentioning
confidence: 99%
“…With the advent of focused ion beam (FIB) milling techniques, it became possible to manufacture specimens in the µm range with sufficient accuracy for mechanical testing at this scale, commonly referred to as micromechanical testing. Specimens of different geometries such as cantilevers [29][30][31][32], tensile specimens [33], micropillars [34][35][36][37], etc can be manufactured with precision using FIB and 5 tested with the help of nanoindenters and micromanipulators. Micro-mechanical testing offers a unique tool to assess the response of thin surface layers, due to its ability to probe mechanical properties of specimens at µm length scales with high spatial resolution.…”
Section: Introductionmentioning
confidence: 99%